Article Review: Potensi Senyawa Xanthone dalam Ekstrak Kulit Manggis (Garcinia Mangostana l.) sebagai Senyawa Aktif Obat - Khuriyah Khuriyah; Vriezka Mierza (Poltekkes Kemenkes Padang, 2025)
The high prevalence of communicable and non-communicable diseases in Indonesia, such as periodontal disease, malaria, diabetes, and Alzheimer’s, highlights the need for safer and more affordable alternative therapies. One promising natural source is mangosteen (Garcinia mangostana L.), which contains xanthone compounds with diverse biological activities. This study aims to review the potential of xanthones from mangosteen pericarp extract as active drug candidates. A comprehensive literature review was conducted by searching articles in Scopus, Google Scholar, and PubMed databases using relevant keywords including “xanthone” and “Garcinia mangostana.” Eligible articles were selected based on inclusion criteria (2014–2024, full-text availability, relevance, and reputable indexing). From 221 identified studies, 9 key articles were analyzed in detail. The findings reveal that xanthone compounds exhibit a wide range of pharmacological activities, including antibacterial, antimalarial, antidiabetic, anticancer, cardioprotective, anti-Alzheimer’s, protective effects against oxidative stress in keratinocytes, and potential COVID-19 therapy through ACE2 and Mpro blockade. These results suggest that xanthones from mangosteen peel hold great potential to be developed as active compounds in modern herbal medicines. Nevertheless, further studies, particularly clinical trials, are required to validate their safety and efficacy.